2018
DOI: 10.1097/gme.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double-blind, placebo-controlled clinical trial for evaluating the efficacy of fractional CO2 laser compared with topical estriol in the treatment of vaginal atrophy in postmenopausal women

Abstract: CO2 vaginal laser alone or in combination with topical estriol is a good treatment option for VVA symptoms. Sexual-related pain with vaginal laser treatment might be of concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
163
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(177 citation statements)
references
References 22 publications
8
163
1
5
Order By: Relevance
“…Likewise, Vera et al conducted a randomized, placebo‐controlled, double‐blind clinical trial in 2015 comparing the results of three controlled groups (45 patients divided into 3 groups of 15): Co2 fractionated laser, topical estrogen, and the combination of both for postmenopausal patients with symptoms of vulvovaginal atrophy. In contrast to the previous study, the laser‐only arm demonstrated an increase in pain in the Sexual Function Index, but an improvement in dyspareunia in the EVA . It is difficult to explain the incongruence of pain results in two studies where the same laser and parameters were used, but some differences are that in the latter study only two sessions of treatment were performed and that the first was not controlled by placebo.…”
Section: Discussionmentioning
confidence: 59%
“…Likewise, Vera et al conducted a randomized, placebo‐controlled, double‐blind clinical trial in 2015 comparing the results of three controlled groups (45 patients divided into 3 groups of 15): Co2 fractionated laser, topical estrogen, and the combination of both for postmenopausal patients with symptoms of vulvovaginal atrophy. In contrast to the previous study, the laser‐only arm demonstrated an increase in pain in the Sexual Function Index, but an improvement in dyspareunia in the EVA . It is difficult to explain the incongruence of pain results in two studies where the same laser and parameters were used, but some differences are that in the latter study only two sessions of treatment were performed and that the first was not controlled by placebo.…”
Section: Discussionmentioning
confidence: 59%
“…However, most stated three laser treatments led to a superior score and sustained results. Four studies used the VMV . Three of these studies reported a significant increase in maturation value, while the fourth reported no difference .…”
Section: Discussionmentioning
confidence: 99%
“…Sixteen studies used the VHIS . All reported a statistically significant improvement, regardless of whether it was one or up to three laser treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the need for randomized, placebo-controlled trials with sham devices is highlighted by the first such trial published 9 . In a study of 45 women, the authors found that, although laser alone or in combination with vaginal estriol was as effective as estriol alone for VVA symptoms, there was an unexpected reported increase in sexual pain in the laser group.…”
mentioning
confidence: 99%